Quality of life of Indonesian adolescents in the time of the COVID-19 pandemic - Herlin Fitriana Kurniawati; Herlin Fitriani Kurniawati (Universitas Aisyiyah Yogyakarta, 2022)
The outbreak of Coronavirus Disease 2019 (COVID-19) in Indonesia has been declared as a public health emergency, which requires some prevention and control efforts as a mitigation strategy. This pandemic requires all activities to be carried out at home including school. This study aims to determine the quality of life of adolescents during the COVID-19 pandemic. This study was conducted using a quantitative approach, and descriptive analytic method. It involved high school/vocational high school students in Kulon Progo who were willing to be respondents as the research subjects and samples. 301 respondents were selected using simple random sampling technique. The research instrument used The World Health Organization Quality of Life (WHOQOL) –BREF. The data were analyzed descriptively by looking at the presented data percentage in the frequency distribution table. The research respondents comprised of 117 male respondents (39%) and 184 female respondents (61%), with an age range of 15-19 years old. 149 respondents (49.5%) were mostly satisfied with their health during the COVID-19 pandemic or having their health in the good category. 121 respondents (40.2%) mostly considered their ability to learn during the COVID-19 pandemic in the average category. 124 respondents (41.2%) who experienced negative feelings, such as feeling blues, anxiety and depression during the COVID-19 pandemic were mostly in the rare category. Most teenagers, 156 respondents (52%), have a good quality of life during the COVID-19 pandemic.